2014
DOI: 10.1039/c4ra11291a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin amyloid fibril formation by ferulic acid, a natural compound found in many vegetables and fruits

Abstract: The highly ordered structures from the self-assembly of proteins/peptides, referred to as amyloid fibrils, are the major cause for many neurodegenerative diseases. Herein, we have analyzed the effect of ferulic acid (FA), one of the most abundant phenolic acids in plants, fruits and vegetables, on the inhibition of insulin (associated with type II diabetes) fibrillation. It was found that the amount of fibril formation was greatly reduced with increasing concentration of FA as evidenced from turbidity measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 70 publications
3
27
0
Order By: Relevance
“…We have previously shown that FA, a phenolic compound, has a capability of inhibiting insulin fibrillation, which was concentration dependent. To grasp the overall inhibitory efficiency of a mixture containing gelatin and FA, we had selected a concentration of FA (0.034 mg mL −1 ) and gelatin (0.3 wt%) at which they elicited an average inhibitory activity when they tested individually. As can be seen from figure 6 A, during the progress of the fibril formation, absorbance at 600 nm is significantly reduced in the presence of gelatin:FA mixture compared to their individual inhibitory efficiency, indicating the less amyloid fibrillation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We have previously shown that FA, a phenolic compound, has a capability of inhibiting insulin fibrillation, which was concentration dependent. To grasp the overall inhibitory efficiency of a mixture containing gelatin and FA, we had selected a concentration of FA (0.034 mg mL −1 ) and gelatin (0.3 wt%) at which they elicited an average inhibitory activity when they tested individually. As can be seen from figure 6 A, during the progress of the fibril formation, absorbance at 600 nm is significantly reduced in the presence of gelatin:FA mixture compared to their individual inhibitory efficiency, indicating the less amyloid fibrillation.…”
Section: Resultssupporting
confidence: 92%
“…Because gelatin is commonly used to make capsules (enclosed shell of medicines), we have also tested the efficiency of a known insulin amyloid inhibitor such as FA, as an example, in the presence of gelatin against insulin fibrillogenesis. We have previously shown that FA, a phenolic compound, has a capability of inhibiting insulin fibrillation, which was concentration dependent. To grasp the overall inhibitory efficiency of a mixture containing gelatin and FA, we had selected a concentration of FA (0.034 mg mL −1 ) and gelatin (0.3 wt%) at which they elicited an average inhibitory activity when they tested individually.…”
Section: Resultsmentioning
confidence: 97%
“…Jayamani et al demonstrated the inhibitory effect of ferulic acid on insulin amyloid fibril formation. The minimum molar ratio of insulin:ferulic acid (1:10) displayed the maximum inhibition of insulin fibrillation approximately 85% [ 131 ]. Ferulic acid prevented the conformational transition from α-helix to β-sheet.…”
Section: Potential Mechanisms Of Action Of Cinnamic Acid and Its Dmentioning
confidence: 99%
“…Ferulic acid prevented the conformational transition from α-helix to β-sheet. Molecular docking analysis revealed that the phenyl, hydroxyl and carboxylic moieties of ferulic acid interact with insulin through hydrogen bonds as well as hydrophobic interactions [ 131 ]. It is proposed that ferulic acid can be considered for delaying the growth of amyloidosis.…”
Section: Potential Mechanisms Of Action Of Cinnamic Acid and Its Dmentioning
confidence: 99%
“…Among all these routes, based on centuries of coexistence between humans and plants, the use of phytochemicals for this purpose has received more attention. Along this line of strategy, the use of phenolic compounds such as curcumin, [11][12][13] gallic acid, 14 ferulic acid, 15 quercetin, 16 etc. have attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%